The effects of Eurycoma longifolia on testosterone and blood pressure in high-fat-fed animal model - Mokhtar R.H.; Al-Joufi F.; Saxena A.K.; Al-Ani I.M.; Talib N.A.; Ku-Zaifah N. (Open Science Publishers LLP Inc., 2024)
Indexed by SCOPUS